2018
DOI: 10.1101/291906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age dependence of systemic bone loss and recovery following femur fracture in mice

Abstract: The most reliable predictor of future fracture risk is a previous fracture of any kind. The etiology of this increased fracture risk is not fully known, but it is possible that fracture initiates systemic bone loss leading to greater fracture risk at all skeletal sites. In this study we investigated systemic bone loss and recovery following femoral fracture in young (3 month old) and middleaged (12 month old) mice. Transverse femur fractures were created using a controlled impact, and whole-body bone mineral d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 56 publications
(63 reference statements)
3
33
0
Order By: Relevance
“…However, because disuse is less likely to be a contributor to hip BMD loss following an upper body fracture, hip bone loss following an upper body fracture may be driven by other non-mechanical mechanisms. In our studies of post-fracture bone loss in mice, we observed considerable systemic inflammation as well as mechanical unloading at early time points post-fracture, along with increased osteoclastogenesis in trabecular bone [19]. These same mechanisms may contribute to post-fracture bone loss in people, since immobility and injury-induced inflammation are operative in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because disuse is less likely to be a contributor to hip BMD loss following an upper body fracture, hip bone loss following an upper body fracture may be driven by other non-mechanical mechanisms. In our studies of post-fracture bone loss in mice, we observed considerable systemic inflammation as well as mechanical unloading at early time points post-fracture, along with increased osteoclastogenesis in trabecular bone [19]. These same mechanisms may contribute to post-fracture bone loss in people, since immobility and injury-induced inflammation are operative in this population.…”
Section: Discussionmentioning
confidence: 99%
“…This bone loss was associated with decreased voluntary movement of mice (mechanical unloading), increased levels of circulating inflammatory cytokines, and increased osteoclast number at early time points (3–4 days) post-injury [19]. This bone loss observed in mice may also occur in elderly individuals post-fracture, since prolonged immobility and inflammation post-fracture in elderly women and men may contribute to fracture risk.…”
Section: Introductionmentioning
confidence: 99%
“…24 Osteoclasts hyperfunction could then increase the risk rating of poor bone healing and fractures. 25,26 Moreover, generalized osteoporosis was reported to negatively influence implant stability and implant failures are mostly due to poor bone quality. 27,28 In recent years, scaffolds combined with specific actives substance (eg vascular endothelial growth factor and bone morphogenetic protein 2) were utilized to regulate cell behaviour in acellular therapy to promote bone formation.…”
Section: Bone Disorders Such As Osteoporosis Have Become One Of Healthmentioning
confidence: 99%
“…This increase in osteoclast-mediated mobilization of calcium can result in a 2-15% reduction in bone mass of intact bones. [42][43][44][45] These metabolic responses to fracture are of extreme clinical relevance as the incidence of clinical or more commonly sub-clinical malnutrition is high in orthopedic trauma patients. 34,46 Malnutrition when present in the context of the hypermetabolic response to trauma can impede healing.…”
Section: Metabolic Response To Fracturementioning
confidence: 99%
“…55 Preventing bone loss in the intact skeleton may have immense clinical utility especially in geriatric patients, considering that posttraumatic bone loss is exacerbated with age. 42 Although these simple interventions can have profound impacts on post-fracture pathophysiology and recovery, poor compliance has been identified as an important factor that may limit the effectiveness of nutritional supplements. 101 Future studies should address the barriers along with strategies to overcome them to inform the best approach to deliver nutritional supplements after fracture.…”
mentioning
confidence: 99%